Topological Vulnerability Analysis of the Mexican Power Grid Using Complex Network Theory - Rivas-Dávalos, Francisco; Sánchez-Jaime, Jorge; Tovar-Hernández, José-Horacio (New Energy Exploitation and Application, 2024)
This study presents a pioneering analysis of the network properties within the Mexican power grid (MXPG). The study included the 400 kV and 230 kV grids. Both grids were analysed independently and as a single combined grid. Based on complex network theory, several topological metrics were calculated, and the vulnerability of the power grid to random failures and intentional attacks was investigated. The MXPG displays several features of small-world networks, namely, a large clustering coeﬃcient and a small average shortest path length. The degree distribution reveals exponential behaviour. Additionally, it was found that the power grid is more vulnerable to targeted attacks on nodes with a high degree than to random failures. In general terms, this study illuminates the intricate structure of the Mexican power grid, shedding light on its structural vulnerabilities, crucial for informing future strategies aimed at enhancing its robustness against potential disruptions.